How can European competition law address market distortions caused by state-owned enterprises? - Mathew Heim (Bruegel, 2019)
This Policy Contribution assesses whether European competition law could be applied more directly to state-owned enterprises that create an unlevel playing field in Europe because of the support they receive from their home governments. This issue has become a priority for many European Union countries and for the European Commission, given its impact on European economic autonomy. Competition law may not be the appropriate tool for addressing the granting of illegal subsidies or other forms of support in third countries, but it could be more effective than previously thought in dealing with the distortive effect of stateowned entities on the EU internal market. If State-Owned Enterprises are not resource-constrained or even profit maximising, they might be unconstrained by competitive pressures, therefore possessing a de-facto level of market power. By adapting existing antitrust theories of harm, such as predatory pricing, to fit the specific nature of SOEs, this Policy Contribution argues that it should be possible to add further tools to the EU's toolbox. In any event, as part of its efforts to address the distortive effects on the internal market of foreign state ownership and subsidies, the European Commission should develop a coherent and proactive competition policy to provide guidance to the market.
Keywords: 330